GERIA PUSAT INDUSTRI BANTEN NGABEN DI BALI PERSPEKTIF SOSIOLOGI KOMODIFIKASI AGAMA - Atmadja, Nengah Bawa (Jurnal Kawistara, 2014)
In the 2000s, banten (offerings) of ngaben (cremation), a ritual of death in Balinese community is obtainedthrough market so it creates the commodification of banten. This condition is caused by the characteristicsof banten as an economic item, so the Balinese especially women is no longer to be able to make banten,and the expanding of market ideology turns someone to be more comfortable buying banten ngaben ratherthan making them independently. This condition provides an opportunity for geria (house of the priest)to develop the industry of banten. This is well corresponded with the ideology prevailing in geria, namelymarket ideology so that they see banten as a source of benefit. The position of geria is stronger than theconsumer of banten because geria dominates various capitals, such as economic, social, cultural, and symboliccapital synergistically. As the result, geria as banten manufacturer controls consumer hegemonically. Thisphenomenon is reflected on the price of banten set by geria and the consumer is just following